Law Enforcement Challenges to Defamation on Social Media - Tista Nabila Ahmad; Dian Ekawaty Ismail; Jufryanto Puluhulawa (Universitas Negeri Gorontalo, 2023)
The aim of this research is to find out and analyze aboutlaw enforcement against perpetrators of defamation through social media in jurisdictionsAs a result of this research, researchers found that first, How is the implementation of law enforcement against perpetrators of defamation via social media by the Gorontalo City Police, after the ITE Law No.19 of 2016, that is the implementation of law enforcement against perpetrators of defamation via social media by Satreskrim. Second, the factors that become obstacles for the police in enforcing the law against perpetrators of defamation through social media in accordance with the ITE Law No. 19 of 2016, namely the obstacles or obstacles lie in the legal constraints themselves, constraints from law enforcement, constraints on facilities and infrastructure, constraints from society, cultural constraints